An Overview of the Isoprenoid Emissions From Tropical Plant Species - Mu, Zhaobin; Llusià, Joan; Zeng, Jianqiang; Zhang, Yanli; Asensio, Dolores; Yang, Kaijun; Yi, Zhigang; Wang, Xinming; Peñuelas, Josep (Frontiers in Plant Science, 2022)
Terrestrial vegetation is the largest contributor of isoprenoids (a group of biogenic volatile organic compounds (BVOCs)) to the atmosphere. BVOC emission data comes mostly from temperate regions, and less is known about BVOC emissions from tropical vegetation, even though it is estimated to be responsible for > 70% of BVOC emissions. This review summarizes the available data and our current understanding of isoprenoid emissions from tropical plant species and the spatial and temporal variation in emissions, which are strongly species-specific and regionally variable. Emission models lacking foliar level data for tropical species need to revise their parameters to account for seasonal and diurnal variation due to differences in dependencies on temperature and light of emissions from plants in other ecosystems. More experimental information and determining how emission capacity varies during foliar development are warranted to account for seasonal variations more explicitly.